CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Simplify the expression 2(a + ab + 3) - ab and find its value when a = 5 and b = - 3.
  1. a + ab + 6 and 1
  2. 2a + 2ab + 6 and - 1
  3. 2a + ab + 6 and - 1
  4. 2a + ab + 6 and 1


Solution

The correct option is D 2a + ab + 6 and 1
2(a + ab + 3) - ab
= 2a + 2ab + 6 - ab
= 2a +( 2ab - ab) + 6
= 2a + ab + 6
Substituting  a = 5, b = - 3 in the above expression,
= 2(5) + (5)(-3) + 6
= 10 - 15 + 6
= 16 - 15
= 1

flag
 Suggest corrections
thumbs-up
 
0 Upvotes



footer-image